Knowledge sharing behaviour among Malaysian students / Hisham Ibrahim Hussein Mallasi - Hisham Ibrahim , Hussein Mallasi (2013)
Knowledge sharing is a social interaction among individuals. People share knowledge for many reasons. Past studies focused mainly on reward system particularly monetary. This may be true for individuals working in organizations. However, there have not been many empirical data that analyses why individual students share knowledge as there is no monetary rewards at stake. Thus, this study aims to investigate the influence of the non-monetary factors (such as enjoy helping others, reputation, self efficacy, interpersonal trust, humility) on knowledge sharing behavior among postgraduate students. In addition, the study also analyses the role of religiosity on knowledge sharing behavior and non monetary factors. Empirical data was collected using a survey questionnaire. The questionnaire was distributed to the postgraduates based on quota sampling method to ensure representativeness of the targeted population. A total of 1683 questionnaires were distributed to six public universities in the Klang Valley. However only 1267 were complete and used for analysis. The results of the analysis illustrated some new findings. One, it was found that humility was factorised into two and was renamed as general humility and scholarly humility whereas previous study is based on humility in general. Two, non monetary factors such as enjoy helping others, self efficacy, interpersonal trust have a significant impact on knowledge sharing while reputation does not. In addition, it was discovered that religiosity plays a moderating role in the relationship between non-monetary factors and knowledge sharing behaviour.